BORROWING WORDS IN THE FIELD OF POLITICS ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
This study examines the phenomenon of complex borrowed words in the realm of politics, focusing on the linguistic and sociopolitical implications of such borrowings. Drawing on a corpus of political discourse from various languages, the analysis reveals the intricate ways in which borrowed words are integrated into political communication and discourse. Through a combination of qualitative and quantitative methods, this research sheds light on the processes of borrowing, adaptation, and semantic extension that characterize the use of complex borrowed words in political contexts. The findings contribute to our understanding of the role of language in shaping political ideologies and power dynamics, highlighting the complex interplay between linguistic diversity and political discourse.